DMF-T index and caries prevalence of international class students of Faculty of Dentistry Universitas Padjadjaran - Lokman, Bonardeen Bin; Fadhil, Richata; Hayati, Ayu Trisna (Padjadjaran Journal of Dentistry, 2013)
Dental caries is a localized destruction of the tooth surface initiated by decalcification of the enamel followed by lysis of organic structure leading to cavity formation. The purpose of this research was to discover the DMF-T index and caries prevalence of all international class students of Faculty of Dentistry of Universitas Padjadjaran. This research was a descriptive study with the survey method. Data from 176 samples (batch 2004 until 2010 students) were taken through clinical examination and questionnaires. The result of this research showed that the average DMF-T index was 2.8, while the caries prevalence was 81.8%. From this research can be concluded that the average DMF-T index of all international class students of Faculty of Dentistry of Universitas Padjadjaran was categorized as moderate, while the caries prevalence was high.